Empowering students with meaningful learning - Jolly, Eric; Fifth International Teaching for Intelligence Conference (Arlington Heights, IL : SkyLight Training and Publishing, 1999)
Eric Jolly discusses the benefits of integrating the joy of discovery across the curriculum and shares methods for designing, implementing, and assessing meaningful curricula for diverse student populations. Presents methods by which schools can create effective learning environments that involve the entire community through an analysis of best practices that model positive interaction between school and community
Executive producer, Ela Aktay ; coordinating producer, Ed Przyzychi ; production assistant, Jo Vuco
Keywords: Classroom environment -- United States; Curriculum planning -- Social aspects -- United States; Minority students -- United States